Enhancement of castor oil biotransformation into aroma by Yarrowia lipolytica mutants - Braga, Adelaide (2013)
The food industry has a great interest in biotechnological production of γ- decalactone by Yarrowia lipolytica, due to its increasing consumers acceptability in comparison with similar products obtained by chemical synthesis. This yeast is able to produce γ-decalactone by transformation of a hydroxylated C18 fatty acid. However, lower yields of γ-decalactone were obtained (up to 4–5 gL-1), mainly due the degradation of newly synthesized lactone and the partial use of ricinoleic acid or intermediate at the C10 level, which is simultaneously the precursor for other γ-lactones. Thus, the purpose of this work is to enhance the biotransformation of castor oil, source of ricinoleic acid, into γ-decalactone exploring different operation mode strategies in bioreactor (batch and fed-batch) and compare the yields obtained with wild type strain with those achieved by mutant strains. Different experiments were conducted in a 3.7-L bioreactor using an aeration rate of 5.1 L min-1, agitation 650 rpm and pH 6.0 (previously optimized conditions [1]). The influence of castor oil concentration and cell density on γ-decalactone production was investigated. Two different cell and castor oil concentrations (30 g L-1 and 60 gL-1) were used for the biotransformation. In the expectation of achieving higher γ-decalactone concentrations, a step-wise fed-batch strategy was also attempted. In a first approach, this study was conducted with Yarrowia lipolytica W29 (ATCC20460) and the highest γ-decalactone productivity of 215.4 mg L-1 h-1 was obtained in a batch mode of operation with 60 g L-1 of cells and 60 g L-1 of castor oil. After that, γ-decalactone production with two Yarrowia lipolytica mutants was studied. Experiments performed with Y. Lipolytica MTLY40-2P, with a deletion of all the POX 3–5 genes and a multicopy insertion of POX2 [2], resulted in an increased accumulation and an inhibition of γ-decalactone degradation. Since this yeast is also known to be a lipase producer and these enzymes catalyze the hydrolysis of triacylglycerides into glycerol and free fatty acids, a Y. lipolytica JMY3010 mutant, that overexpress extracellular lipase by the LIP2 gene (encoded the main extracellular lipase activity) cloned under the control of the TEF promoter [3], as also used. With these different approaches is possible to increase aroma productivity and a greater enhance in γ-decalactone production was achieved (up to 7-9 gL-1) through conjugation of a bioprocess optimization and genetic engineering approach.